Trends in the contributions of atopic family history to pediatric food sensitization and allergy - Fang, Heping; Ma, Zhuoying; Chen, Lin; Xian, Ruoling; Wang, Juan; Chen, Jing; Li, Haiqi; Hu, Yan (Frontiers in Pediatrics, 2022)
Objective: Family history of atopic diseases (FHA) contributes to food allergy (FA). But little is known whether FHA primarily increases IgE–mediated, non–IgE–mediated FA, or both. And the trends in the contributions of FHA to food sensitization (FS) and FA remain unclear. We aim to clarify the associations among FHA, FS and FA and to understand the trends in the contributions of FHA to FS and FA. Methods: We used chi–square test and mediating effect model to analyze the associations among FHA, FS and FA through comparisons between two cross–sectional investigations on FA in children under 2 years old in 2009 and 2019. Results: In 2009 and 2019, the positive FHA proportion tended to be increasing without significance (28.9% to 31.6%, P=0.39). Subgroup analysis showed the FS rate in FA group decreased significantly (37/39 to 44/62, P=0.003). In 2009, the FS rate and FA prevalence were higher in FHA(+) group than in FHA(–) group (26% vs. 14.7%, P=0.008 and 15% vs. 7.7%, P=0.03), and FS had a complete mediating effect on the association between FHA and FA (Z=2.54, P=0.011), but the results lost significance in 2019. Conclusions: The association between FHA and FA was completely mediated by FS, which means FHA mainly increases IgE–mediated FA. And the contributions of FHA to FS and FA tended to be stabilized or even diminished, which means FHA alone could no longer be enough to screen high–risk children.